Composite aerogel reinforced epoxy resin material as well as preparation method and application thereof

By using graphene oxide and sodium alginate in epoxy resin, combined with the effect of silane coupling agent, the effect of improving the tensile strength and shear strength of the epoxy resin is achieved, the problem of strength reduction in the prior art is solved, and the preparation process is simplified.

CN119752098AActive Publication Date: 2025-04-04CHIZHOU KECHENG NEW MATERIALS DEV CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411684947.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-04-04
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

In the prior art, when preparing an epoxy resin composite material by adding graphene oxide and sodium alginate, there are problems of decreasing tensile strength and shear strength.

Method used

A composite aerogel made from graphene oxide aqueous dispersion and sodium alginate aqueous solution as raw materials is used as the additive material, and is mixed with epoxy resin A component and silane coupling agent to improve the strength of the material through hydrogen bonding and cross-linking.

Benefits of technology

It effectively improves the tensile strength and shear strength of epoxy resin, solves the problem of strength reduction in the existing technology, and simplifies the preparation process and broadens the application prospects of epoxy resin composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752098A_ABST
    Figure CN119752098A_ABST
Patent Text Reader

Abstract

The embodiment of the invention relates to the technical field of composite materials, and particularly discloses a composite aerogel reinforced epoxy resin material as well as a preparation method and application thereof, and the composite aerogel reinforced epoxy resin material comprises the following raw materials: composite aerogel, an epoxy resin component A and a silane coupling agent. According to the embodiment of the invention, the composite aerogel prepared from the raw materials of the aqueous dispersion of graphene oxide and the aqueous solution of sodium alginate is used as an additive material and is matched with the silane coupling agent, so that hydrogen bonds and cross-linking effects are generated among active groups on the surface of graphene oxide, sodium alginate, the coupling agent and epoxy resin; the tensile strength and the shear strength of the material are effectively improved, and the problem that the tensile strength and the shear strength are reduced when the epoxy resin composite material is prepared by adding graphene oxide and sodium alginate in the prior art is solved. Moreover, the preparation method provided by the embodiment of the invention is simple and has a wide market prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiment of the present invention belongs to the technical field of composite materials, and specifically relates to a composite aerogel reinforced epoxy resin material and a preparation method and application thereof. Background Art

[0002] With the continuous development of material technology, epoxy resin, as a commonly used polymer material, has been widely used in chemical industry, aviation, aerospace and other fields due to its good physical properties and chemical stability. Aerogel, as a lightweight nanoporous material with broad application prospects, is also called dry gel, which means that most of the solvent is removed from the gel, leaving less liquid in the gel, or the medium filling the gel space network is gas, and the appearance is solid. It is characterized by low density, high specific surface area, high porosity, and nanostructure. In addition, graphene is a two-dimensional sheet material with a honeycomb lattice structure. It not only has good conductivity, stability and high specific surface area, but also has excellent flexibility and mechanical strength. Although graphene oxide has a similar structure to graphene, because graphene oxide contains polar groups such as epoxy, carboxyl, and hydroxyl, it has new characteristics such as strong dispersibility, compatibility, hydrophilicity, and easy surface modification. Sodium alginate, as a biomass polysaccharide material, has excellent biocompatibility and degradability, is easy to prepare into a gel material, and has many applications in the hospital field.

[0003] At present, in the market, aerogel can be added to epoxy resin to significantly improve its thermal insulation performance, mechanical properties and durability to meet the needs of more application scenarios. For example, in the prior art, graphene oxide aerogel is prepared by a sol-gel method, and then a low-viscosity epoxy resin is added to the formed aerogel to prepare an epoxy resin composite material with graphene oxide as the skeleton, which effectively improves the storage modulus. Although epoxy resin composite materials can be prepared using graphene oxide, sodium alginate, etc. as additives, most of them use graphene oxide or sodium alginate alone as raw materials and are prepared using aerogel technology. Moreover, when preparing composite materials by adding graphene oxide, sodium alginate, etc. to epoxy resin, there is often a problem of reduced tensile strength and / or shear strength due to the reduced degree of crosslinking between the additive and the epoxy resin. Therefore, the above-mentioned prior art solutions have the following defects: in the prior art, when epoxy resin composite materials are prepared by adding graphene oxide and sodium alginate, there is a problem of reduced tensile strength and shear strength. Summary of the invention

[0004] The purpose of the embodiment of the present invention is to provide a composite aerogel reinforced epoxy resin material to solve the problem of reduced tensile strength and shear strength when preparing epoxy resin composite materials by adding graphene oxide and sodium alginate in the prior art mentioned in the above background technology.

[0005] To achieve the above objectives, the embodiments of the present invention provide the following technical solutions:

[0006] A composite aerogel reinforced epoxy resin material comprises the following raw materials: composite aerogel, epoxy resin component A, and silane coupling agent; wherein the composite aerogel is prepared using graphene oxide aqueous dispersion and sodium alginate aqueous solution as raw materials.

[0007] Preferably, in the composite aerogel, the mass content of graphene oxide is 30%-90%.

[0008] Further preferably, the composite aerogel is prepared by freeze-drying and post-crosslinking with calcium chloride using graphene oxide aqueous dispersion and sodium alginate aqueous solution as raw materials.

[0009] Still further preferably, the epoxy resin component A comprises the following raw materials in parts by weight: 2-20 parts by weight of epoxy resin component; 1-10 parts by weight of curing agent; 60-90 parts by weight of conductive filler; and 0-2.5 parts by weight of defoaming agent.

[0010] Another object of the embodiment of the present invention is to provide a method for preparing a composite aerogel-reinforced epoxy resin material, wherein the method for preparing a composite aerogel-reinforced epoxy resin material specifically comprises the following steps:

[0011] An appropriate amount of composite aerogel and epoxy resin component A are weighed and placed in a container, and then a silane coupling agent is added to mix evenly, and then placed in a mold and baked at 180-220° C. for 1-3 hours to obtain the composite aerogel reinforced epoxy resin material.

[0012] Another object of an embodiment of the present invention is to provide an application of the above-mentioned composite aerogel reinforced epoxy resin material in preparing a composite material.

[0013] Compared with the prior art, the embodiments of the present invention have the following beneficial effects:

[0014] The composite aerogel-reinforced epoxy resin material provided by the embodiment of the present invention uses composite aerogel, epoxy resin component A, and silane coupling agent reasonably, and uses composite aerogel prepared from graphene oxide aqueous dispersion and sodium alginate aqueous solution as raw materials as an additive material, and cooperates with the effect of silane coupling agent, so that the active groups on the surface of graphene oxide and sodium alginate, silane coupling agent, and epoxy resin can produce hydrogen bonds and cross-linking effects, thereby improving the tensile strength and shear strength of epoxy resin, and solving the problem of reduced tensile strength and shear strength when preparing epoxy resin composite materials by adding graphene oxide and sodium alginate in the prior art. Moreover, the preparation method of the composite aerogel-reinforced epoxy resin material provided by the embodiment of the present invention is simple, can be used to prepare other types of resin-based composite materials, and has broad market prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention.

[0016] Figure 1 Infrared spectra of different composite aerogel samples provided in one embodiment of the present invention.

[0017] Figure 2 This is a scanning electron microscope image of different composite aerogel reinforced epoxy resin materials provided by another embodiment of the present invention.

[0018] Figure 3 This is a scanning electron microscope image of GO / SA-1 / epoxy resin A component provided by another embodiment of the present invention.

[0019] Figure 4 This is a scanning electron microscope image of GO / SA-2 / epoxy resin A component provided by another embodiment of the present invention. DETAILED DESCRIPTION

[0020] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention and the accompanying drawings. Obviously, the following embodiments will help those skilled in the art to further understand the embodiments of the present invention, but do not limit the embodiments of the present invention in any form. It should be pointed out that for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the embodiments of the present invention. These all belong to the protection scope of the embodiments of the present invention.

[0021] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0022] First of all, it should be noted that epoxy resin, as a commonly used polymer material, has good physical properties and chemical stability. Usually, in order to further improve its performance and meet the needs of more application scenarios, aerogel can be added to epoxy resin to significantly improve its thermal insulation, mechanical properties and durability. For example, in the prior art, graphene oxide aerogel was prepared by a sol-gel method, and then a low-viscosity epoxy resin was added to the molded aerogel to prepare an epoxy resin composite material with graphene oxide as the skeleton, which effectively improved the storage modulus. Graphene aerogel with a Janus structure was synthesized by a compression-annealing assembly method, and then a multifunctional graphene aerogel / epoxy resin composite material with a Janus structure was prepared, which can greatly improve the conductivity of the composite material.

[0023] Secondly, it should be noted that, in the current prior art, although epoxy resin composite materials can be prepared using graphene oxide, sodium alginate, etc. as additives, most of them are prepared using graphene oxide or sodium alginate alone as raw materials, using aerogel technology, and it is relatively rare to use graphene oxide and sodium alginate as raw materials. Moreover, because graphene oxide (GO) contains polar groups such as epoxy, carboxyl, and hydroxyl, it has new characteristics such as strong dispersibility, compatibility, hydrophilicity, and easy surface modification. Sodium alginate (SA) belongs to biomass polysaccharide materials, has excellent biocompatibility and degradability, and is easily prepared into gel materials. Epoxy resin has excellent physical and mechanical and electrical insulation properties, as well as good material bonding properties, and is widely used in various fields such as coatings, composite materials, casting materials, adhesives, etc. Although, composite materials can be prepared by adding materials in epoxy resin to enhance tensile strength and shear strength. However, when preparing composite materials by adding graphene oxide, sodium alginate, etc. to epoxy resin, there is often a problem of reduced tensile strength due to reduced crosslinking between the added materials and the epoxy resin.

[0024] Generally speaking, the tensile strength of common epoxy resins is between 40-100MPa. The tensile strength of epoxy resin plays an important role in materials science. For example, epoxy resin itself has high strength and hardness. Epoxy resin can be injected into wood to fill gaps, so that the wood can improve mechanical properties and stability. In the application of composite materials, epoxy resin composites have high tensile strength and elastic modulus, which makes epoxy resin composites perform well in applications requiring high strength and high rigidity. In addition, epoxy resin has good chemical resistance and electrical insulation properties, and can maintain stable performance in harsh environments. In short, designing a method for preparing epoxy resin composites using graphene oxide and sodium alginate has become a problem that needs to be solved urgently.

[0025] Therefore, in order to solve the problem of reduced tensile strength and shear strength when preparing epoxy resin composite materials by adding graphene oxide and sodium alginate in the prior art, an embodiment of the present invention provides a composite aerogel reinforced epoxy resin material and a preparation method and application thereof. The composite aerogel reinforced epoxy resin material is specifically a graphene oxide / sodium alginate composite aerogel reinforced epoxy resin material, which includes the following raw materials:

[0026] Composite aerogel, epoxy resin component A, silane coupling agent;

[0027] The composite aerogel is prepared using graphene oxide aqueous dispersion and sodium alginate aqueous solution as raw materials.

[0028] In the embodiment of the present invention, the composite aerogel reinforced epoxy resin material adopts a composite aerogel prepared by using a graphene oxide aqueous dispersion and a sodium alginate aqueous solution as raw materials as an additive material, adds it to the epoxy resin component A, and cooperates with the effect of a silane coupling agent. Through effective regulation of the ratio, the active groups on the surface of the graphene oxide can generate hydrogen bonds and cross-linking effects with the sodium alginate, coupling agent, and epoxy resin, thereby improving the tensile strength and shear strength of the epoxy resin, and solving the problem of reduced tensile strength and shear strength when preparing epoxy resin composite materials by adding graphene oxide and sodium alginate in the prior art. Although graphene oxide and sodium alginate are used at the same time, the tensile strength and shear strength can also be effectively improved, and the preparation method is simple. Compared with the use of graphene oxide or sodium alginate alone, the preparation technology of epoxy resin composite materials is broadened.

[0029] It should be noted that, at present, in the prior art, graphene oxide or sodium alginate is usually used alone to prepare epoxy resin composite materials, because the use of graphene oxide and sodium alginate at the same time usually results in a decrease in tensile strength and shear strength. The embodiment of the present invention utilizes the characteristics of graphene oxide and sodium alginate to prepare graphene oxide / sodium alginate composite aerogel, and mixes it with epoxy resin to explore the effect of composite aerogels with different graphene oxide contents on the mechanical properties of epoxy resin. Through effective regulation of the ratio, hydrogen bonds and cross-linking can be generated between the active groups on the surface of graphene oxide and sodium alginate, coupling agents, and epoxy resin, thereby improving the tensile strength and shear strength of the epoxy resin.

[0030] As another preferred embodiment of the present invention, the composite aerogel is a porous graphene oxide / sodium alginate composite aerogel (GO / SA) prepared by freeze-drying and post-crosslinking with calcium chloride using graphene oxide aqueous dispersion and sodium alginate aqueous solution as raw materials.

[0031] As another preferred embodiment of the present invention, the freeze drying method is to perform freeze drying at -10°C to -100°C in a freeze dryer and take out when the temperature reaches room temperature.

[0032] Preferably, the freeze drying temperature of the freeze drying method is -62.8°C. Specifically, after the graphene oxide aqueous dispersion and the sodium alginate aqueous solution are mixed as raw materials to form a uniform gel, the gel is placed in a freeze dryer for freeze drying (-62.8°C), and taken out when the temperature is at room temperature.

[0033] As another preferred embodiment of the present invention, the post-crosslinking method of calcium chloride is to soak in a saturated calcium chloride alcohol solution after freeze-drying, and then wash and dry.

[0034] Furthermore, the calcium chloride post-crosslinking method is to soak it in a 14% saturated calcium chloride alcohol solution after freeze drying, leave it at room temperature for a period of time, then wash it with alcohol to remove the residual calcium chloride, and then put it into an electric constant temperature blast drying oven for drying.

[0035] As another preferred embodiment of the present invention, in the composite aerogel, the mass content of graphene oxide is 30%-90%.

[0036] Preferably, in the composite aerogel, the mass content of graphene oxide is one of 50%, 60%, 70%, 80%, and 85%.

[0037] As another preferred embodiment of the present invention, in the composite aerogel, the mass content of graphene oxide is 45%-55%.

[0038] Preferably, in the composite aerogel, the mass content of graphene oxide is 50%.

[0039] Further preferably, the preparation method of the composite aerogel is to weigh 0.2432g of reagent-grade graphene oxide aqueous dispersion at room temperature and disperse it in 12ml of sodium alginate aqueous solution with a mass content of 2%. Add a magnet to a beaker and place it in a heat-collecting constant temperature heating magnetic stirrer for stirring (r=20, T=40min / piece, room temperature) until a uniform gel is formed. Then pour the uniform gel into a mold and place it in a freeze dryer for freeze drying (-62.8°C), and take it out when the temperature is at room temperature. In order to ensure complete cross-linking of sodium alginate, soak the freeze-dried gel with a 14% saturated calcium chloride alcohol solution and place it at room temperature for 8 hours. Wash it three times with alcohol to remove the residual calcium chloride. In order to completely volatilize the alcohol, place the aerogel in an electric constant temperature blast drying oven set at 40°C and dry it for 12 hours to obtain a composite aerogel material (GO / SA).

[0040] As another preferred embodiment of the present invention, the epoxy resin component A comprises the following components by weight: 2-20 parts by weight of epoxy resin component; 1-10 parts by weight of curing agent; 60-90 parts by weight of conductive filler; and 0-2.5 parts by weight of defoaming agent.

[0041] Specifically, epoxy resin is a high molecular polymer and also a thermosetting resin. It is usually a polycondensation product of epichlorohydrin and bisphenol A or polyol. Due to the chemical activity of the epoxy group, it can be opened with a variety of compounds containing active hydrogen, cured and cross-linked to form a network structure.

[0042] Preferably, the epoxy resin component is any one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, hydrogenated bisphenol A epoxy resin, and tetraglycidylamine epoxy resin.

[0043] As another preferred embodiment of the present invention, the defoaming agent is any one or more of 6201, BYK-141 or BYK-053.

[0044] As another preferred embodiment of the present invention, the curing agent is any one or more of m-phenylenediamine, diaminodiphenylmethane, diaminodiphenyl sulfone, and m-xylylenediamine.

[0045] As another preferred embodiment of the present invention, the conductive filler can be common conductive materials such as carbon black, silver powder or nano-silicon dioxide and other nano-powder fillers. The specific selection can refer to the products in the prior art and is not limited here. Carbon black can usually be used as the conductive filler.

[0046] As another preferred embodiment of the present invention, the epoxy resin component A may further include an appropriate amount of a curing accelerator, wherein the curing accelerator is one or more of 2-ethyl-4-methylimidazole, 2,4,6-tris(dimethylaminomethyl)phenol, boron trifluoride-triethylamine complex, etc. Usually, the amount of the curing accelerator added is 4-15% of the weight of the epoxy resin component.

[0047] As another preferred embodiment of the present invention, the silane coupling agent can be a vinyl silane coupling agent, such as A151 (vinyl triethoxysilane) and A171 (vinyl trimethoxysilane); an amino silane coupling agent, such as Si-550 (amino functional silane); an epoxy silane coupling agent, such as KH-550γ-aminopropyl triethoxysilane and KH-560 (γ-glycidyl ether oxypropyl trimethoxysilane); a thiol silane coupling agent, such as Si-69 (bis-[γ-(triethoxysilyl)propyl] tetrasulfide); or a diamine silane coupling agent, such as Si-780 (difunctional diamine silane). The specific selection can be made according to the needs.

[0048] Further preferably, the silane coupling agent is silane coupling agent KH-550. Since epoxy resin has poor hydrophilicity, the compatibility between aerogel and epoxy resin is improved by adding a coupling agent.

[0049] The embodiment of the present invention further provides a method for preparing a composite aerogel-reinforced epoxy resin material, and the method for preparing a composite aerogel-reinforced epoxy resin material specifically comprises the following steps:

[0050] An appropriate amount of composite aerogel and epoxy resin component A are weighed and placed in a container, and then a silane coupling agent is added to mix evenly, and then placed in a mold and baked at 180-220° C. for 1-3 hours to obtain the composite aerogel reinforced epoxy resin material.

[0051] Preferably, the method for preparing the composite aerogel reinforced epoxy resin material comprises the following steps:

[0052] 1) At room temperature, weigh 0.2432g, 0.3645g, 0.5571g, 0.9612g, and 1.4300g of reagent-grade graphene oxide aqueous dispersion, respectively, and disperse them in 12ml of a 2% sodium alginate aqueous solution (the mass content of graphene oxide is 0.24%, 0.40%, 0.89%, 1.06%, and 1.20%, respectively). Add a magnet to a beaker, and place it in a heat-collecting constant temperature heating magnetic stirrer for stirring (r=20, T=40min / piece, room temperature) until a uniform gel is formed.

[0053] 2) Pour the uniform gel into a mold and put it into a freeze dryer for freeze drying (-62.8°C), and take it out when the temperature is at room temperature. Soak the freeze-dried gel in a 14% saturated calcium chloride alcohol solution and place it at room temperature for 8 hours. Wash it three times with alcohol to remove the residual calcium chloride. In order to completely volatilize the alcohol, put the aerogel into an electric constant temperature blast drying oven set at 40°C and dry it for 12 hours to obtain a composite aerogel, in which the mass content of graphene oxide is 50%, 60%, 70%, 80%, and 85% respectively (corresponding to composite aerogels prepared by using 0.2432g, 0.3645g, 0.5571g, 0.9612g, and 1.4300g reagent-grade graphene oxide aqueous dispersion, respectively).

[0054] 3) Weigh an appropriate amount of the above composite aerogel and an equal amount of epoxy resin component A respectively, put them into a beaker, and add an appropriate amount of silane coupling agent KH-550 into the beaker four times, and stir evenly. Pour the mixed material of aerogel and epoxy resin component A in the beaker into a mold, and bake at 200°C for 2h to obtain a composite aerogel reinforced epoxy resin material.

[0055] The embodiment of the present invention also provides a composite aerogel reinforced epoxy resin material prepared by using the above-mentioned method for preparing the composite aerogel reinforced epoxy resin material.

[0056] The embodiment of the present invention also provides an application of the above-mentioned composite aerogel reinforced epoxy resin material in the preparation of composite materials. In particular, it is suitable for the preparation of resin-based composite materials. Specifically, thermosetting resins, thermoplastic resins, and various modified or blended matrices can be used as component materials, and the composite aerogel or composite aerogel reinforced epoxy resin material in the embodiment of the present invention is used as a reinforcing material to improve the tensile strength and shear strength of the composite material.

[0057] The technical effects of the composite aerogel reinforced epoxy resin material of the embodiment of the present invention are further described below by listing specific embodiments.

[0058] It should be noted that in the following embodiments, the following instruments are mainly used:

[0059] Analytical balance, Shimadzu International Trading (Shanghai) Co., Ltd.; heat-collecting constant temperature heating magnetic stirrer (model DF-101S), Bangsi Instrument Technology (Shanghai) Co., Ltd.; electric constant temperature blast drying oven (model DHG-9140A), Shanghai Sanfa Scientific Instrument Co., Ltd.; infrared spectrometer (model Nicolet iS10), Nicolet Instruments, USA; freeze dryer (model SCIENTZ-12N), Ningbo Xinyun Biotechnology Co., Ltd.; X-ray diffractometer (model DX-2700), Dandong Haoyuan Instrument Co., Ltd.; Phenom desktop scanning electron microscope (model Phenom Pro), Funa Scientific Instrument (Shanghai) Co., Ltd.; microcomputer-controlled electronic universal testing machine (model WDW-30A), Jinan Kairui Testing Machine Manufacturing Co., Ltd.; thermogravimetric analyzer (model HCT), Beijing Hengjiu Scientific Instrument Factory.

[0060] Example 1

[0061] A composite aerogel, specifically a graphene oxide / sodium alginate composite aerogel prepared by taking graphene oxide aqueous dispersion and sodium alginate aqueous solution as raw materials.

[0062] In this embodiment, the preparation method of the composite aerogel specifically includes the following steps:

[0063] 1) At room temperature, weigh 0.2432 g of reagent-grade graphene oxide aqueous dispersion and disperse it in 12 ml of 2% sodium alginate aqueous solution. Add a magnet to a beaker and place it in a heat-collecting constant temperature heating magnetic stirrer for stirring (stirring speed 20 r / min, room temperature) until a uniform gel is formed.

[0064] 2) Pour the uniform gel into the mold and put it into a freeze dryer for freeze drying (-62.8°C), and take it out when the temperature is at room temperature. In order to ensure the complete cross-linking of sodium alginate, soak the freeze-dried gel in a 14% saturated calcium chloride alcohol solution and leave it at room temperature for 8 hours. Wash it three times with alcohol to remove the residual calcium chloride. In order to make the alcohol completely volatilize, put the aerogel into an electric constant temperature blast drying oven set at 40°C and dry it for 12 hours to obtain a composite aerogel material, in which the mass content of graphene oxide is 50%, marked as GO / SA-1.

[0065] Example 2

[0066] Compared with Example 1, except that the amount of reagent-grade graphene oxide aqueous dispersion is 0.3645 g, the other conditions are the same as Example 1. The prepared composite aerogel material is marked as GO / SA-2, in which the mass content of graphene oxide is 60%.

[0067] Example 3

[0068] Compared with Example 1, except that the amount of reagent-grade graphene oxide aqueous dispersion is 0.5571 g, the other conditions are the same as Example 1. The prepared composite aerogel material is marked as GO / SA-3, in which the mass content of graphene oxide is 70%.

[0069] Example 4

[0070] Compared with Example 1, except that the amount of reagent-grade graphene oxide aqueous dispersion is 0.9612 g, the other conditions are the same as Example 1. The prepared composite aerogel material is marked as GO / SA-4, in which the mass content of graphene oxide is 80%.

[0071] Example 5

[0072] Compared with Example 1, except that the amount of reagent-grade graphene oxide aqueous dispersion is 1.4300 g, the other conditions are the same as Example 1. The prepared composite aerogel material is marked as GO / SA-5, in which the mass content of graphene oxide is 85%.

[0073] Example 6

[0074] In this embodiment, appropriate amounts of GO / SA-1, GO / SA-2, GO / SA-3, GO / SA-4, GO / SA-5 composite aerogels prepared in Examples 1-5 and an equal amount of epoxy resin component A are weighed and placed in 5 beakers, and an appropriate amount of silane coupling agent KH-550 is added to each beaker four times and stirred evenly. Then, the mixed materials of the composite aerogel and epoxy resin component A in the 5 beakers are used to prepare a shearing tool and cast into a tensile specimen mold, and baked at 200°C for 2h to obtain 5 composite aerogel-enhanced epoxy resin materials containing corresponding components, each of which has a prepared shearing tool and a tensile specimen.

[0075] Among them, the specific proportions of 5 composite aerogel reinforced epoxy resin materials containing corresponding components are shown in Table 1, and the formulas of serial numbers 1, 2, 3, 4, and 5 are marked as GO / SA-1 / epoxy resin component A, GO / SA-2 / epoxy resin component A, GO / SA-3 / epoxy resin component A, GO / SA-4 / epoxy resin component A, and GO / SA-5 / epoxy resin component A, respectively.

[0076] Table 1 Formula table for different concentration gradient designs

[0077]

[0078] According to Table 1, the composite aerogel reinforced epoxy resin material prepared with GO / SA-1 as raw material is marked as GO / SA-1 / epoxy resin component A, and the mass content of GO / SA-1 in the raw material is 0.5%, the mass content of epoxy resin component A is 99.49%, and the mass content of silane coupling agent KH-550 is 0.01%. The corresponding other formulas can refer to GO / SA-1 / epoxy resin component A.

[0079] In this embodiment, the components of the epoxy resin component A are calculated by mass percentage and are as follows: 15% epoxy resin component; 8% curing agent; 75% conductive filler; 2% defoaming agent; wherein the epoxy resin component is bisphenol A type epoxy resin, the defoaming agent is BYK-141, and the curing agent is m-phenylenediamine.

[0080] Example 7

[0081] In this example, the GO / SA-1 sample of Example 1 was used as a test sample, and the structural groups in the components of the composite aerogel were analyzed by infrared spectroscopy. At the same time, graphene oxide (marked as GO) and sodium alginate (marked as SA) were used as comparative references, and the structural groups in the components of the aerogel were analyzed by infrared spectroscopy under the same conditions. Specifically, the KBr tablet method was used to perform infrared characterization on GO, SA and GO / SA-1 composite materials, respectively, with a scanning range of 400cm -1 ~4000cm -1 The infrared spectrum obtained is as follows Figure 1 shown.

[0082] from Figure 1 It can be seen that in the infrared spectrum of GO, 3452cm -1 The broad absorption peaks near 1645 cm are the stretching vibration absorption peaks of the hydroxyl group (-OH) in the molecule. -1 、1493cm -1 and 1157cm -1 The absorption peaks at 3460cm are due to the vibration absorption peaks of C=C, C-OH, and COC in the molecule. It can be seen that graphene oxide contains hydrophilic functional groups such as hydroxyl and epoxy groups, which can participate in related chemical reactions. For sodium alginate, 3460cm -1 The broad absorption peak near 1647 cm is due to the stretching vibration of hydroxyl (-OH). -1 The absorption peak at 2941cm is due to the symmetrical and asymmetrical stretching vibrations of the carboxyl group (-COOH) in the molecular structure. -1 The absorption peak at 3394 cm is caused by the CH stretching vibration on the six-membered ring in sodium alginate. For graphene oxide / sodium alginate composite aerogel GO / SA-1, the absorption peak at 3394 cm-1 、1595cm -1 and 1410cm -1 The peaks at the bottom are the hydroxyl (-OH) stretching vibration absorption peak, the asymmetric stretching vibration peak and the symmetric stretching vibration peak of the carboxyl (-COOH) group. By comparing the infrared spectra of GO, SA, and GO / SA-1, it can be seen that the vibration peak absorption peaks of the composite aerogel all move toward the low wave number direction, indicating that adding graphene oxide to the sodium alginate system will not have much impact on the original molecular structure. The change in the peak wave number of the vibration peak may be caused by the hydrogen bonding between graphene oxide and the sodium alginate macromolecules.

[0083] Example 8

[0084] The surface morphology of the aerogel samples prepared in Examples 1-5 was analyzed using a scanning electron microscope (SEM) image as shown in FIG. Figure 2 As shown. Among them, Figure 2 Figure (a) is a digital photo of GO / SA-1, GO / SA-2, GO / SA-3, GO / SA-4, and GO / SA-5 prepared in Examples 1-5. It can be seen from the actual objects in the beaker that the GO / SA series composite aerogel materials can maintain a relatively complete cubic structure. Figure 2 Figures (b), (c), (d), (e) and (f) are scanning electron microscope (SEM) images of GO / SA-1, GO / SA-2, GO / SA-3, GO / SA-4 and GO / SA-5, respectively. Figure 2 (b) and (c) are GO / SA-1 and GO / SA-2 composite aerogel materials, respectively. From the figure, we can clearly see the honeycomb network structure with more pores, but the porous structure is somewhat disordered, which may be caused by the uneven dispersion of graphene oxide and sodium alginate. Figure 2 (c) is a GO / SA-3 composite aerogel material. From the figure, it can be found that the number of pores is significantly reduced and there is a layer superposition phenomenon. Figure 2 (e) and (f) are GO / SA-4 and GO / SA-5 composite aerogel materials, respectively. It is obvious from the figure that graphene oxide is stacked and piled up. The main reason may be that when the amount of GO in the composite aerogel material is too large, the GO sheets will overlap, making it difficult to combine with SA. Figure 2 From the SEM image, we can see that there are some small particles on the GO / SA composite aerogel material. These small particles are probably caused by the calcium chloride not being completely washed away during the preparation process.

[0085] Example 9

[0086] In this embodiment, the mechanical properties of the composite aerogel-reinforced epoxy resin materials marked as GO / SA-1 / epoxy resin component A, GO / SA-2 / epoxy resin component A, GO / SA-3 / epoxy resin component A, GO / SA-4 / epoxy resin component A, and GO / SA-5 / epoxy resin component A in Example 6 were tested. Specifically, the shear strength and tensile strength of the composite aerogel-reinforced epoxy resin materials were analyzed using a universal testing machine, and the tensile specimens of the prepared 5 groups of composite aerogel-reinforced epoxy resin materials were subjected to mechanical property tests using a universal testing machine. At the same time, the epoxy resin component A was used as a reference sample to perform a mechanical property test of the tensile specimen under the same conditions. The specific mechanical property test results are shown in Table 2.

[0087] Table 2 Mechanical properties test results

[0088] Sample Tensile strength / MPa Shear strength / MPa Epoxy resin A component 45.26 11.56 GO / SA-1 / Epoxy Resin A Component 50.60 14.48 GO / SA-2 / Epoxy Resin A Component 44.55 11.22 GO / SA-3 / epoxy resin component A 42.15 10.25 GO / SA-4 / epoxy resin component A 40.66 9.15 GO / SA-5 / Epoxy Resin A Component 39.85 8.63

[0089] According to the data in Table 2, it can be seen that in GO / SA-2 / epoxy resin A component, GO / SA-3 / epoxy resin A component, GO / SA-4 / epoxy resin A component, and GO / SA-5 / epoxy resin A component, when the aerogel material content is 0.5% of the aerogel / epoxy resin composite material, the tensile strength and shear strength of the epoxy resin composite material with a graphene oxide content of 50% in the aerogel material (i.e., GO / SA-1 / epoxy resin A component) are the largest, and the tensile strength and shear strength of the epoxy resin composite material with a graphene oxide content of 85% in the composite aerogel material (i.e., GO / SA-5 / epoxy resin A component) are the smallest. The tensile strength and shear strength of GO / SA-1 / epoxy resin A component are higher than those of pure epoxy resin material. The main reason may be that the active groups on the surface of graphene oxide generate hydrogen bonds and crosslinks with SA, coupling agent, and epoxy resin, which improves the strength and shear strength of epoxy resin. However, it was also observed that as the content of graphene oxide in the composite aerogel material increased, the tensile strength and shear strength of the aerogel / epoxy resin composite material gradually decreased. The main reason may be that when the amount of GO in the composite aerogel material is too large, the GO sheets will overlap, weakening its nano-size effect, and the degree of cross-linking with the epoxy resin is reduced, resulting in a decrease in tensile strength.

[0090] Example 10

[0091] In this embodiment, the microstructure of the composite aerogel reinforced epoxy resin material is analyzed, and the scanning electron microscope (SEM) image obtained by the microstructure analysis is as follows: Figure 3 , Figure 4 As shown, Figure 3 It is a composite aerogel reinforced epoxy resin material marked as GO / SA-1 / epoxy resin A component. Figure 4 It is a composite aerogel reinforced epoxy resin material marked as GO / SA-2 / epoxy resin A component. Through analysis, it was found that the cross-section scan of pure epoxy resin showed a uniform and smooth morphology, while other images showed a relatively rough morphology. This is due to the stress concentration, crack deflection and partial filler agglomeration caused by the added composite aerogel material. Figure 3 and Figure 4 The cross-sectional particle distribution of the composite aerogel-reinforced epoxy resin material is relatively uniform overall. However, the cross-sectional particle distribution of the composite aerogel-reinforced epoxy resin material marked as GO / SA-3 / epoxy resin component A, GO / SA-4 / epoxy resin component A, and GO / SA-5 / epoxy resin component A shows obvious agglomeration. The main reason may be that with the increase of graphene oxide content, the amount of GO in the composite aerogel material is too large, and internal superposition occurs, resulting in weakened cross-linking ability with epoxy resin and obvious self-agglomeration.

[0092] In the embodiment of the present invention, graphene oxide aqueous dispersion and sodium alginate (SA) are used as raw materials, and graphene oxide / sodium alginate composite aerogel is obtained by freeze drying. Using SEM and FTIR test analysis, it can be seen that a composite aerogel reinforced epoxy resin material with a porous structure and a composite aerogel surface have functional groups such as hydroxyl and epoxy groups, but the content of graphene oxide has a greater influence on the porous structure of the composite aerogel. Then the prepared composite aerogel material is extruded and blended with epoxy resin, and finally a tensile specimen is prepared by an injection machine. Using a universal testing machine for test analysis, it can be seen that when the amount of composite aerogel added is 0.5%, the content of graphene oxide in the composite aerogel material is 50%, and the tensile strength and shear strength of the prepared composite aerogel reinforced epoxy resin material are optimal. The main reason may be the hydrogen bonds and crosslinking between the active groups on the surface of graphene oxide and SA, coupling agents, and epoxy resins.

[0093] Embodiment 11

[0094] Compared with the composite aerogel reinforced epoxy resin material marked as GO / SA-1 / epoxy resin A component in Example 6, everything else is the same except that the freeze-drying is carried out at -10°C.

[0095] Example 12

[0096] Compared with the composite aerogel reinforced epoxy resin material marked as GO / SA-1 / epoxy resin A component in Example 6, everything else is the same except that the freeze-drying is carried out at -100°C.

[0097] Embodiment 13

[0098] Compared with the composite aerogel reinforced epoxy resin material marked as GO / SA-1 / epoxy resin A component in Example 6, except that the mass content of graphene oxide in the composite aerogel is 45%, all other aspects are the same.

[0099] Embodiment 14

[0100] Compared with the composite aerogel reinforced epoxy resin material marked as GO / SA-1 / epoxy resin A component in Example 6, except that the mass content of graphene oxide in the composite aerogel is 55%, all other aspects are the same.

[0101] Embodiment 15

[0102] Compared with the composite aerogel reinforced epoxy resin material marked as GO / SA-1 / epoxy resin A component in Example 6, except that the epoxy resin component is bisphenol F epoxy resin, everything else is the same.

[0103] Example 16

[0104] Compared with the composite aerogel reinforced epoxy resin material marked as GO / SA-1 / epoxy resin A component in Example 6, except that the epoxy resin component is a tetraglycidylamine type epoxy resin, everything else is the same.

[0105] Embodiment 17

[0106] Compared with the composite aerogel reinforced epoxy resin material marked as GO / SA-1 / epoxy resin A component in Example 6, everything else is the same except that the epoxy resin component is a mixture of bisphenol A epoxy resin and bisphenol F epoxy resin in equal weight proportions.

[0107] Embodiment 18

[0108] Compared with the composite aerogel reinforced epoxy resin material marked as GO / SA-1 / epoxy resin A component in Example 6, except that the epoxy resin component is a mixture of bisphenol A epoxy resin, bisphenol F epoxy resin, hydrogenated bisphenol A epoxy resin, and tetraglycidylamine epoxy resin in equal weight proportions, everything else is the same.

[0109] According to the above results, it can be seen that the embodiment of the present invention uses graphene oxide aqueous dispersion (GO) and sodium alginate (SA) as raw materials, and obtains a porous graphene oxide / sodium alginate composite aerogel (GO / SA) by freeze drying and calcium chloride post-crosslinking. The surface micromorphology, functional group structure, etc. of the composite aerogel and the mechanical properties of the aerogel / epoxy resin composite material were characterized and analyzed using scanning electron microscopy (SEM), infrared spectroscopy (IR) and universal testing machine, and the porous structure changes of the composite aerogel prepared by different graphene oxide concentrations and the influence of mechanical properties doped into epoxy resin were explored. Through comparative experiments, it can be seen that when the added graphene oxide content is 50%, the porous structure of the composite aerogel is obvious, and the maximum tensile strength of the composite aerogel reinforced epoxy resin material is 50.6Mpa, and the maximum shear strength is 14.48Mpa. The embodiment of the present invention adopts a composite aerogel prepared by using graphene oxide aqueous dispersion and sodium alginate aqueous solution as raw materials as an additive material, adds it to the epoxy resin A component, and cooperates with the effect of a silane coupling agent. Through the reasonable use of raw materials and effective regulation of the proportion, hydrogen bonds and cross-linking can be generated between the active groups on the surface of graphene oxide and sodium alginate, coupling agents, and epoxy resin, thereby improving the tensile strength and shear strength of the epoxy resin, and solving the problem of reduced tensile strength and shear strength when preparing epoxy resin composite materials by adding graphene oxide and sodium alginate in the prior art. Moreover, the preparation method provided by the embodiment of the present invention is simple, effectively broadens the preparation technology of epoxy resin composite materials, and has broad market prospects.

[0110] In addition, it should be noted that most of the current existing technologies use graphene oxide as an aerogel material to add to epoxy resin, or simply prepare sodium alginate / graphene oxide composite aerogel. For example, a Chinese patent with announcement number CN 106853296B discloses an oil-water separation type sodium alginate / graphene oxide composite aerogel, which mainly uses the composite aerogel for oil-water separation, has high separation efficiency, and high salt resistance, and can be applied to high-salt marine environments. The embodiment of the present invention is to prepare sodium alginate / graphene oxide aerogel material, and then apply it to epoxy resin to achieve the effect of improving the mechanical properties of epoxy resin.

[0111] Finally, it should be noted that the silane coupling agent KH-550 and the like in the embodiments of the present invention are all products of existing manufacturers. For example, among other main reagents: the graphene oxide aqueous dispersion is a reagent-grade graphene oxide aqueous dispersion, produced by Suzhou Carbon Graphene Technology Co., Ltd.; sodium alginate (AR grade), Aladdin Chemical Reagent Co., Ltd.; anhydrous calcium chloride (AR grade), Tianjin Dengke Chemical Reagent Co., Ltd.; anhydrous ethanol (AR grade), Sinopharm Chemical Reagent Co., Ltd. The above are all conventional additives in the production of epoxy resin composite materials, and they are selected according to specific needs, and are not described here.

[0112] The above is a detailed description of the preferred embodiments of the present invention, describing the basic principles, main features and advantages of the present invention. However, those skilled in the art should understand that the embodiments of the present invention are not limited to the above embodiments. The above embodiments and descriptions are only preferred examples of the present invention and are not intended to limit the present invention. Various changes can be made within the knowledge of ordinary technicians in this field without departing from the purpose of the embodiments of the present invention. It is not necessary and impossible to list all the embodiments here. The obvious changes or modifications derived from this are still within the scope of protection of the embodiments of the present invention.

Claims

1. A composite aerogel reinforced epoxy resin material, characterized in that: The composite aerogel reinforced epoxy resin material comprises the following raw materials: composite aerogel, epoxy resin component A, and silane coupling agent; wherein the composite aerogel is prepared using graphene oxide aqueous dispersion and sodium alginate aqueous solution as raw materials.

2. The composite aerogel reinforced epoxy resin material according to claim 1, characterized in that: In the composite aerogel, the mass content of graphene oxide is 30%-90%.

3. The composite aerogel reinforced epoxy resin material according to claim 2, characterized in that: In the composite aerogel, the mass content of graphene oxide is 45%-55%.

4. The composite aerogel reinforced epoxy resin material according to claim 3, characterized in that: The composite aerogel is prepared by using graphene oxide aqueous dispersion and sodium alginate aqueous solution as raw materials through freeze drying and calcium chloride post-crosslinking.

5. The composite aerogel reinforced epoxy resin material according to claim 4, characterized in that: In the preparation method of the composite aerogel, the freeze-drying method is to perform freeze-drying at a temperature between -10°C and -100°C; the calcium chloride post-crosslinking method is to soak the aerogel in a saturated calcium chloride alcohol solution and then wash and dry the aerogel.

6. The composite aerogel reinforced epoxy resin material according to claim 5, characterized in that: The epoxy resin component A comprises the following raw materials by weight: 2-20 parts by weight of epoxy resin component; 1-10 parts by weight of curing agent; 60-90 parts by weight of conductive filler; 0-2.5 parts by weight of defoaming agent.

7. The composite aerogel reinforced epoxy resin material according to claim 6, characterized in that: The epoxy resin component is any one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, hydrogenated bisphenol A epoxy resin and tetraglycidylamine epoxy resin.

8. The composite aerogel reinforced epoxy resin material according to claim 7, characterized in that: The curing agent is any one or more of m-phenylenediamine, diaminodiphenylmethane, diaminodiphenyl sulfone and m-xylylenediamine.

9. A method for preparing a composite aerogel reinforced epoxy resin material according to any one of claims 1 to 8, characterized in that: The following steps are involved: An appropriate amount of composite aerogel and epoxy resin component A are weighed and placed in a container, and then a silane coupling agent is added to mix evenly, and then placed in a mold and baked at 180-220° C. to obtain the composite aerogel reinforced epoxy resin material.

10. Use of the composite aerogel reinforced epoxy resin material as claimed in claim 1 or 2 or 3 or 4 or 5 or 6 or 7 or 8 in preparing a resin-based composite material.

Citation Information

Patent Citations

  • An oil-water separation type sodium alginate / graphene oxide composite aerogel and its preparation method

    CN106853296B

  • Preparation method of functionalized graphene oxide / epoxy resin nanocomposite

    CN103627139A

  • Modified graphene oxide and epoxy resin composite material and method for preparing same

    CN105906842A

  • Method for preparing flame retardant epoxy resin from modified graphene

    CN108641292A

  • Graphene oxide / sodium alginate / carrageenan three-dimensional compound network gel spheres and preparation method and application thereof

    CN110115986A